3D printed PCL scaffold reinforced with continuous biodegradable fiber yarn: A study on mechanical and cell viability properties. (March 2020) - Hedayati, Seyyed Kaveh; Behravesh, Amir Hossein; Hasannia, Sadegh; Bagheri Saed, Arvin; Akhoundi, Behnam
Abstract: In this study, poly (ε‐caprolactone) (PCL) scaffolds were printed and reinforced, simultaneously, with biodegradable poly glycolic acid (PGA) suture yarn, as a continuous reinforcing fiber, in the Fused Deposition Modeling (FDM) 3D printing process. Albeit PCL is a suitable material for biomedical applications, its low mechanical properties, and low degradation rate have limited its usage. A biocompatible suture yarn was used as the reinforcing material to enhance the mechanical properties and biodegradation characteristics, via an innovative method of continuous fiber embedding in the FDM process. The reinforced PCL samples were 3D printed with the setting porosity value of 60% and 0°/60°/120° lay-down pattern. The mechanical and biological properties of the scaffolds were tested to prove the effectiveness of the produced scaffolds for bone substitute purposes. Mechanical properties assessments showed that with a 22 vol.% suture yarn content in the 3D printed PCL scaffolds, the tensile strength, and elastic modulus remarkably increased up to 374% and 775%, respectively. The degradation of the reinforced PCL was 20 times higher than that of the non-reinforced PCL samples, after ten weeks, dominated by the fiber degradation phenomenon. After three days of cell culture, the proliferation assay of the built scaffovd the non-toxicity of the reinforced PCL. Highlights: A novel PCL-based biocomposite is introduced and manufactured with continuous bio-fiber reinforcement. Embedding continuous biodegradable fiber yarn was successfully carried out via an FDM 3D printer to produce scaffolds. Mechanical properties of the reinforced samples were evaluated, and a major increase in tensile properties was achieved. Scaffold reinforced with biodegradable fiber was successfully printed, with favorite biological properties.